Development of novel PET probe [11C](R, R)HAPT and its stereoisomer [11C](S, S)HAPT for vesicular acetylcholine transporter imaging: A PET study in conscious monkey. Issue 7 (12th April 2014) - Nishiyama, Shingo; Ohba, Hiroyuki; Kobashi, Tatsuhiro; Nakamasu, Yumi; Nakao, Hidekazu; Ogata, Tokutaro; Kitashoji, Takeru; Tsukada, Hideo
ABSTRACT Carbon‐11‐labeled (R, R)trans‐8‐methyl‐2‐hydroxy‐3‐[4‐[2‐aminophenyl]piperizinyl]‐tetralin ([11C](R, R)HAPT) and its stereoisomer [11C](S, S)HAPT were developed for imaging vesicular acetylcholine transporters (VAChTs), exclusively located in presynaptic cholinergic neurons. Both positron emission tomography (PET) probes were evaluated in the brain of conscious monkey (Macaca mulatta) using high‐resolution PET. Time‐activity curves (TACs) of [11C](R, R)HAPT peaked within 5 min after the injection in all regions except the caudate and putamen, both of which showed peaks around 20 min postinjection. The regional distribution patterns of [11C](R, R)HAPT determined as total distribution volume (Vt) were highest in the putamen, high in the caudate, intermediate in the amygdala, hippocampus, and thalamus, lower in the cingulate gyrus and frontal, temporal, and occipital cortices, and lowest in the cerebellum. In contrast, the distribution and TACs of [11C](S, S)HAPT were homogeneous in all regions. The uptake of [11C](R, R)HAPT was reduced by 1 mg/kg (−)‐vesamicol, a specific VAChT antagonist, in all regions except the cerebellum, but not by 0.1 mg/kg SA4503, a specific sigma‐1 receptor agonist. These results well reflect the in vitro affinity assessments using rat cerebral membranes. They also demonstrate that [11C](R, R)HAPT is a potential PET probe for noninvasive and quantitative imaging of VAChT in the living brain. Synapse 68:283–292, 2014. © 2014 Wiley Periodicals, Inc.